A minimal common outcome measure set for COVID-19 clinical research. Issue 8 (August 2020) - ,; Marshall, John C; Murthy, Srinivas; Diaz, Janet; Adhikari, Neil; Angus, Derek C; Arabi, Yaseen M; Baillie, Kenneth; Bauer, Michael; Berry, Scott; Blackwood, Bronagh; Bonten, Marc; et al.
Summary: Clinical research is necessary for an effective response to an emerging infectious disease outbreak. However, research efforts are often hastily organised and done using various research tools, with the result that pooling data across studies is challenging. In response to the needs of the rapidly evolving COVID-19 outbreak, the Clinical Characterisation and Management Working Group of the WHO Research and Development Blueprint programme, the International Forum for Acute Care Trialists, and the International Severe Acute Respiratory and Emerging Infections Consortium have developed a minimum set of common outcome measures for studies of COVID-19. This set includes three elements: a measure of viral burden (quantitative PCR or cycle threshold), a measure of patient survival (mortality at hospital discharge or at 60 days), and a measure of patient progression through the health-care system by use of the WHO Clinical Progression Scale, which reflects patient trajectory and resource use over the course of clinical illness. We urge investigators to include these key data elements in ongoing and future studies to expedite the pooling of data during this immediate threat, and to hone a tool for future needs.